Magnetized Seeds and Structured Water: Effects on Resilience of Velvet Bean Seedlings (Mucuna pruriens) under Deficit Irrigation - Ramsey, Craig L. (Journal of Basic & Applied Sciences, 2023)
A custom-built water generator supplied structured water (SW) for applying the deficit irrigation treatments to velvet bean plants (Mucuns pruriens). The objectives of the study were to 1) determine the effects of magnetized seed treatment on velvet bean plants, 2) determine the effects of magnetized and hydroxylated water treatments on velvet bean plants, and 4) determine the effects of deficit irrigation, using three soil moisture levels, on velvet bean plants. The optimal water-saving treatment was magnetized seeds plus 10 MT + HWT. This treatment had a 226% increase in transpiration and a 22% increase in water vapor concentration in the intercellular airspace for the low soil moisture watering schedule. The three study factors in the optimal seed and water treatment had a synchronistic effect for enhancing metabolic efficiency by increasing whole plant WUE by 87% and carbon assimilation efficiency by 66% in the low soil moisture schedule. Plants irrigated with SW water and grown from magnetized seeds had enhanced resilience to high water stress conditions by maintaining adequate levels of biologically structured water. The rapid deactivation of a suite of highly interconnected defense activities in the optimal seed and water treatments implies that the plants exhibit macroscopic coherence properties. Coherence at the macroscopic level resulted in complex synchronization between metabolic efficiency, plant health, and deactivation of a suite of regulatory defenses in plants exposed to high water stress.